Dual diagnosis of neurobrucellosis and Anti-LGI1 encephalitis: a rare case report - Chuyan Yang; Ying Liu; Yongzhong Lin; PeiYu Shi; Jing Tan (BMC Infectious Diseases)
Abstract Background Anti-LGI1 encephalitis is a subtype of autoimmune encephalitis characterised by cognitive dysfunction, psychiatric disorders, faciobrachial dystonic seizures, and hyponatraemia. However, its precise pathogenesis remains unclear. Brucellosis, a zoonotic disease prevalent globally, poses a significant threat to public health; nevertheless, the nonspecific nature of its clinical symptoms often results in diagnostic delays. Case presentation We report the case of a middle-aged male patient diagnosed with anti-LGI1 antibody encephalitis through antibodies in serum and CSF combined with neurobrucellosis through serum antibodies and CSF NGS. Additional testing for paraneoplastic-related and demyelinating-related antibodies, CSF and blood culture yielded negative results, helping rule out other pathogens and etiologies. The patient exhibited symptom improvement after effective antimicrobial and immunomodulatory therapies. Conclusions This case raises awareness of autoimmune encephalitis following Brucella infection, revealing a potential association between Brucella infection and anti-LGI1 antibody encephalitis. Brucella may be a triggering factor for anti-LGI1 antibody encephalitis; however, more cases are needed to confirm our findings.